Prioritizing Selective Laser Trabeculoplasty: A Sustainable Glaucoma Treatment Option for Pakistan. - Ibrahim, Muhammad; Ahmad, Muhammad; Khattak, Anusha (Journal of the Pakistan Medical Association, 2025)
Glaucoma is a progressive optic neuropathy characterized by retinal ganglion cell degeneration and optic nerve damage, often associated with elevated intraocular pressure (IOP). The global burden of glaucoma is rising, particularly in South Central Asia, where cases are projected to nearly double by 2040. Current management strategies primarily rely on IOP-lowering medications such as beta-blockers, prostaglandin analogues, and carbonic anhydrase inhibitors. However, the high cost and adherence challenges associated with long-term pharmacological therapy necessitate alternative solutions to alleviate financial and healthcare burdens while ensuring optimal clinical outcomes. Selective Laser Trabeculoplasty (SLT) has emerged as a promising first-line treatment for open-angle glaucoma (OAG) and ocular hypertension. Utilizing a Q-switched, frequency-doubled Nd:YAG laser (532 nm), SLT selectively targets pigmented trabecular meshwork cells, enhancing aqueous humor outflow without causing collateral thermal damage. The Laser in Glaucoma and Ocular Hypertension (LiGHT) Trial demonstrated that SLT provides sustained IOP control without medications in approximately 70% of cases. Furthermore, SLT significantly reduces the need for glaucoma and cataract surgeries, with minimal adverse effects such as ocular discomfort, dry eye, and mild conjunctivitis. Additional studies, including the West Indies Glaucoma Laser Study (WIGLS) and a randomized controlled trial conducted in Tanzania, further support SLT’s efficacy in comparison to conventional IOP-lowering medications, such as 0.5% Timolol eye drops. These findings have influenced clinical guidelines, leading to the incorporation of SLT as a first-line treatment in recommendations by the European Glaucoma Society and the UK’s National Institute for Health and Care Excellence (NICE). Beyond its clinical advantages, SLT offers significant economic benefits. As a one-time outpatient procedure, SLT reduces long-term dependence on costly medications, alleviating financial strain on both patients and healthcare systems. In resource-limited settings like Pakistan, where medication adherence is hindered by limited pharmacy access and low awareness, SLT provides a practical solution by eliminating the need for daily eye drops. Establishing the long-term cost-effectiveness of SLT could further support its integration into standard glaucoma management protocols. In conclusion, SLT presents a sustainable and effective approach for managing OAG, particularly in low-income regions. By reducing disease progression, minimizing the need for frequent follow-ups, and lowering surgical intervention rates, SLT offers a viable alternative to traditional medication-based therapy. To maximize its potential, equitable access to laser treatment should be prioritized in tertiary care hospitals, enabling wider adoption and improved patient outcomes across underserved populations.